Making Queer Asiatic Worlds: Performance and Racial Interaction in North American Visual Novels - Patterson, Christopher B. (American Literature, 2022)
This paper argues that video games expose the presumptions separating “Asian America” and “Asia” in the traditional senses of isolation, origination, and presumed distance. It does so by focusing on the most “Asiatic” genre of video games today, the North American visual novel, which offers a counterdiscourse to normative modes of play and attempts to offer utopic spaces to reflect upon the “real” genres of race and neo–Cold War geopolitics. Using theories of performance from Dorinne Kondo and others, the author shows how queer indie visual novels are primarily aspirational, in that they build queer, utopic, and seemingly anti-racist worlds through the Asiatic space of the visual novel form. In so doing, they also allow players to explore the Asiatic as a means of repairing the traumas and distances of American imperial cultures. The article analyzes four visual novels to make this argument: three by non-racially-identifying North American designers—Doki Doki Literature Club! (2017) by Dan Salvato, Analogue: A Hate Story (2012) by Christine Love, and Heaven Will Be Mine (2018) by Aevee Bee—and Butterfly Soup (2017), a game by the queer Asian/American designer Brianna Lei. If games make the boundaries of Asia and America irrelevant, visual novels explore this irrelevance through Asiatic irreverence.
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; _Nettoyé